Can stimulating ownership increase fertility: Evidence from housing interventions in China - Xin Zhang; Dongxue Wu; William A.V. Clark (Proceedings of the National Academy of Sciences, 2026)
Declining fertility and the emergence of very low TFR’s in the Asian economies has increased the focus on how to change the direction of the fertility trend. Several countries in Europe and Asia have explored a variety of stimulus packages to increase the overall TFR. In this research we review those policies and examine one of those interventions which has the potential to stimulate fertility—the role of access to housing. The core of housing approaches to stimulating fertility is to make housing more accessible and to use various forms of credit assistance with the aim of making ownership easier and more attractive to young families. The research asks how effective are these approaches to reversing the decline in fertility? And, are they a solution to very low fertility? The results provide some evidence that the focus on housing stimulus packages may increase fertility although most successfully for socioeconomically advantaged households.